DETERMINAN PETANI MENCURAHKAN TENAGANYA DI LUAR USAHATANI KARET DI DESA LEKIS REJO KECAMATAN LUBUK RAJA KABUPATEN OKU - Johan Adi Winarno, Fifian Permata Sari (Program Studi Agribisnis Fakultas Pertanian Universitas Baturaja, 2026)
The development of rubber plantations in OKU Regency plays a crucial role, both historically and technically. Ironically, the community faces the problem of increasingly low rubber prices and low rubber production, resulting in many rubber farmers devoting their energy to activities outside of rubber farming to meet family needs. This study aims to analyze the determinants of farmers devoting their energy to activities outside of rubber farming. This study was conducted in Lekis Rejo Village, Lubuk Raja District, OKU Regency. The location was determined purposively. The research method used in this study was a survey method. The sampling method used in the study was a simple random sampling method. The number of samples taken was 30 out of 258 population members, or a percentage of 12 percent. Data obtained from the field were processed through analysis using simple linear regression. The results showed that the variable of land area significantly influenced the outflow of farmer work outside of rubber farming in Lekis Rejo Village, Lubuk Raja District, while the rubber price had no significant effect.